2008
DOI: 10.3892/or.19.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Oral paclitaxel chemotherapy for brain tumors: Ideal combination treatment of paclitaxel and P-glycoprotein inhibitor

Abstract: Abstract. Oral chemotherapy has many advantages over parenteral chemotherapeutics administration. To use the advantages of the oral chemotherapy and maximize anti-tumor effects of the chemotherapeutic agent, we designed HM30181A (a P-glycoprotein inhibitor) and a paclitaxel oral co-administration chemotherapeutic method. HM30181A is used to aid paclitaxel absorption from gut lumen into blood and to inhibit paclitaxel exclusion out of the brain tumor mass by endothelial cells, which inhibits paclitaxel access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Our study is in agreement with the previous reports that demonstrate Elacridar [35] and Valspodar [10], the strong inhibitors of P-gp, are highly effective in increasing the delivery of TX across the BBB and significantly reducing tumor volume in glioblastoma xenografts. Recently, an oral combination therapy using the P-gp inhibitor HM30181A and TX significantly regressed tumor volume by inhibiting TX efflux in animal model of glioblastoma [11], thereby lending support to the possibility of either VPA ? TX or VPA ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is in agreement with the previous reports that demonstrate Elacridar [35] and Valspodar [10], the strong inhibitors of P-gp, are highly effective in increasing the delivery of TX across the BBB and significantly reducing tumor volume in glioblastoma xenografts. Recently, an oral combination therapy using the P-gp inhibitor HM30181A and TX significantly regressed tumor volume by inhibiting TX efflux in animal model of glioblastoma [11], thereby lending support to the possibility of either VPA ? TX or VPA ?…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the commercial formulation of 6 mg/ml (7 mM) TX in 1:1 mixture of the solvents Cremophor EL Ò (CrEL, polyoxyethylated castor oil) and ethanol has systemic toxicity, side effects, and short time stability, and is associated with hypersensitivity reactions [8]. TX is a substrate for the P-gp [9] and co-administration of the P-gp inhibitor PSC833 [10] or HM30181A [11] with TX has shown significant therapeutic efficacy in brain tumor.…”
Section: Introductionmentioning
confidence: 99%
“…It has now been shown that elacridar and tariquidar are not P-gp-specific inhibitors, but at higher concentrations also inhibit BCRP [41–43]. A recent study also demonstrated that oral, bi-weekly co-administration of the new P-gp inhibitor HM30181A with paclitaxel decreased tumor volume of K1735 melanoma brain metastases and U-87 MG glioblastoma in cancer animal models [44]. …”
Section: P-glycoprotein In Brain Cancermentioning
confidence: 99%
“…Another methodology aimed at increasing permeability of chemotherapeutic agents across the CNS, and which has shown promise in the preclinical setting, is inhibition of BBB efflux transporters such as P-glycoprotein (P-gp) [69,70]. Unfortunately, P-gp inhibitors also target the drug metabolizing cytochrome P4503A (CYP3A) leading to alterations in clearance of chemotherapeutic drugs and increased toxicity [69,71]; a limitation that will have to be addressed before continuing with clinical assessment of this approach, if it is used at all.…”
Section: Preclinical Models Of Brain Metastatic Disease As Tools Tmentioning
confidence: 99%
“…Unfortunately, P-gp inhibitors also target the drug metabolizing cytochrome P4503A (CYP3A) leading to alterations in clearance of chemotherapeutic drugs and increased toxicity [69,71]; a limitation that will have to be addressed before continuing with clinical assessment of this approach, if it is used at all. Similar preclinical successes have been observed by inducing disruption of BBB by means of hypotonic solutions such as mannitol [72].…”
Section: Preclinical Models Of Brain Metastatic Disease As Tools Tmentioning
confidence: 99%